ANALYSIS OF BANKS OF UKRAINE IN STOCK MARKET (Socio-economic relations in the digital society, 2019)
The article is devoted three directions of the bank in the stock market: as an issuer, an investor and as its professional member are investigated. External and internal factors aff ecting the banking activity in the security market are identified. The theoretical foundations of the bank activity with the securities are considered.The analysis of security transactions in the banking institutions is implemented. Carrying out the investments in the stock market, banks set the purpose to get profi ts from their investments in securities received by the bank interest, dividends and growth in market value of securities; receiving profi t from providing services to clients with securities transactions; expanding the sphere of infl uence of the bank and attracting new customers through capital of companies and organizations. It is investigated that the share of transactions with securities in the active operations of the banking system is not very big. It is due to the balanced policy of the bank management on investments in equity instruments, in sufficient development of securities market in Ukraine and lack of reliable instruments for financial investments.
Keywords: securities of banks; emission operations of banks; investment operations of banks; brokerage of banks; portfolio of securities; infrastructure of stock market